Altered oxylipin levels in human vitreous indicate imbalance in pro-/anti-inflammatory homeostasis in proliferative diabetic retinopathy. (January 2022) - Zhao, Tantai; Wang, Yanbin; Guo, Xiaojian; Li, Huiling; Jiang, Wenmin; Xiao, Yangyan; Deng, Bin; Sun, Yun
Abstract: Proliferative diabetic retinopathy (PDR) is an advanced stage of diabetic retinopathy (DR), characterized by retinal neovascularization. It is a progressive fundus disease and a severe complication of diabetes that causes vision impairment. Hyperglycemia-induced persistent low-grade inflammation is a crucial factor underlying the pathogenesis of DR-associated damage and contributing to the progression of PDR. Highly enriched polyunsaturated fatty acids (PUFAs) in the retina are precursors to oxidized metabolites, namely, oxylipins, which exert pro-inflammatory or anti-inflammatory (resolving) effects under different pathological conditions and have been implicated in diabetes. To evaluate differences in oxylipin levels in the vitreous obtained from PDR and non-diabetic subjects, we performed a targeted assessment of oxylipins. A total of 41 patients with PDR and 22 non-diabetic control subjects were enrolled in this study. Vitreous humor obtained during routinely scheduled vitrectomy underwent a targeted but unbiased screening for oxylipins using mass spectrometry-based lipidomics. We found 21 oxylipins showing statistically significant differences in their levels between PDR and non-diabetic subjects (p < 0.05). Lipoxygenase (LOX)- and cytochrome P450 (CYP)- derived oxylipins were the most affected, while cyclooxygenase (COX) oxylipins were affected to a lesser extent. When categorized by their precursor PUFAs, ±19, 20-EpDPE, a CYP product of docosahexaenoic acid (DHA) and 12S-HETE, a LOX product of arachidonic acid (ARA), were increased by the largest magnitude. Moreover, of these 21 oxylipins, 7 were considered as potential biomarkers for discriminating PDR patients from the non-diabetic controls. Our results indicate that altered oxylipin levels in the vitreous implicate an underlying imbalanced inflammation-resolution homeostasis in PDR. Highlights: PDR is a severe complication of diabetes that causes vision impairment. PUFAs in the retina are precursors to oxylipins, which exert pro-inflammatory or anti-inflammatory effects. We found 21 oxylipins significantly different between PDR and non-diabetic subjects. Of these 21, seven were considered potential biomarkers for PDR patients. Altered oxylipin levels in vitreous implicated an underlying imbalanced inflammation-resolution homeostasis in PDR.